EVALUASI PARAMETER QUALITY OF SERVICES (QOS) LAYANAN JARINGAN INTERNET MENGGUNAKAN STANDAR TIPHON (STUDI KASUS : PT VALIDATA TEKNOLOGI) - Abdurahman, Dede; Idris, Yona Sri; Nurdiana , Nunu (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
The reliability of the internet network at West Java International Airport (BIJB) Kertajati, managed by PT Validata Teknologi, is a vital component for operational continuity. However, the current evaluation method, which only relies on speed tests and ping tests, is considered inadequate because it does not measure important technical parameters such as actual jitter and throughput, and is performed in a very short duration, making it less representative. This study aims to comprehensively evaluate the internet service's QoS by designing a systematic testing scheme based on the TIPHON standard. The research methodology uses an Action Research approach, where testing is performed with Wireshark software to record data traffic on a 20 Mbps dedicated internet service across seven distribution switches during upload and download activities to Google Drive. The results of the data analysis show that the average values for throughput, packet loss, and delay parameters reached a 'Very Good' category (index 4), while the jitter parameter was categorized as 'Good' (index 3). Thus, the overall quality of the internet network service is concluded to be in the 'High' category, with a final average index of the four parameters of 3.7, in accordance with the TIPHON standard.